MAKNA METAFORIS DALAM PUISI “SAJAK PERTEMUAN MAHASISWA” KARYA W.S. RENDRA MELALUI TINJAUAN SEMANTIK STEPHEN ULLMANN - Roosmawanto, Narendra Brahmantyo Karnamarhaendra; Suswandi, Irwan (MIMESIS, 2023)
This research aims to describe the metaphorical meaning contained in the poem titled "Sajak Pertemuan Mahasiswa" as explained by Stephen Ullmann (1962). Ullmann categorizes metaphors into four types: anthropomorphic metaphor, animal metaphor, concrete-to-abstract metaphor, and synesthesia metaphor. The method used in this research is qualitative research. This qualitative research method uses content analysis to focus on studying literary works. Then, the writer uses library techniques to collect references from books and scientific works to support this research. This technique is continued with the use of note technique, namely numeric technique, in every methapor category. As for the presentation of research results, the author uses an informal method, namely the presentation of data in ordinary words, as a medium to convey the contents of this research. By categorizing the metaphorical meanings that have been collected, the writer discovers that the most categories are anthropomorphic metaphors and metaphors from concrete to abstract, whereas no data with related meanings is found in synesthesia metaphors.